Outcomes of pregnancies in patients with Gaucher Disease: The experience of a center of excellence on rare metabolic Disease-Gaucher Disease, in Greece. (November 2020) - Komninaka, Veroniki; Flevari, Pagona; Marinakis, Theodoros; Karkaletsis, Georgios; Malakou, Lina; Repa, Konstantina
Abstract: Objective: Pregnancy is reported to exacerbate manifestations in women with Gaucher Disease (GD). The objective of our study was to examine the outcome of pregnancies of Caucasian women with GD in a Greek Center of Excellence on GD. Study design: Fifteen GD women were enrolled. All data were collected by questionnaire: fertility, normal pregnancies, spontaneous-elective-therapeutic abortions, maternal -neonatal status, birth weight and chromosomal abnormalities. Results: Forty-one pregnancies were reported among 15 women: mean conception age (±SD) 27.7 ± 5.8years (range 17–42years). Thirty-seven conceptions were spontaneous, 4 were after in vitro fertilization (IVF). Twenty three out of the 41 (56.1 %) pregnancies were normal. Eleven out of the 41 (26.8 %) pregnancies resulted in spontaneous abortions, 3 out of 41 (7.3 %) in elective and 3 out of 41 (7.3 %) in therapeutic abortions. Therapeutic abortions were due to worsening of GD manifestations, fetal chromosomal abnormalities and GD type 2 embryo. Nine out of 15 women had maternal complications: gestational diabetes, splenomegaly, hepatomegaly, thrombocytopenia, osteoporosis and postpartum hemorrhage. Twenty three out of the 41 pregnancies resulted in live births. Nine out of the 23 (39.1 %) deliveries were caesarian sections and 14 out of 23 (60.9 %) were vaginal. The total number of neonates was 24 (14 females / 10 males). Mean gestational age on delivery (± SD) was 35.9 ± 3.1 weeks (range 26−38 w). Average female birth weight (±SD) was 2671.4 ± 851.6 g (range 900−4100 grams) and male was 3333 ± 996.4 g (range 1930−4700 grams). Nine out of 24 (37.5 %) neonates had low birth weight. Average low birth weight (±SD) was 1931.1 ± 420.52 g (range 900−2300 grams). Twenty out of the 24 (83.3 %) neonates were healthy. Four out of 24 neonates had neonatal complications: two neonates had GD type 1, one had GD type 3 and one neonate died two days after delivery (it was born at 26 weeks). Four neonates were hospitalized in incubators at the intensive neonatal care unit due to low birth weight. Thirty-nine women did not receive enzyme replacement therapy for GD during pregnancy, while, in two pregnancies, treatment was discontinued during the first trimester and re-administered after that. Mean first menarche age (±SD) was 13.6 ± 0.7 years. Thirteen out of 15 women were menopausal, mean menopausal age (± SD) 466 ± 2.6 years. Conclusion: Most of GD women experience uncomplicated pregnancies and deliver normal, healthy infants, although the rate of complications and the rate of abortions is high in this population.